Protocol for Isolation of Golgi Vesicles from Human and Animal Hearts by Flotation through a Discontinuous Sucrose Gradient - Estefanía Tarazón; Manuel Portolés; Esther Roselló-Lletí (STAR Protocols, 2020)
Summary: Detailed study of cellular organelles requires their isolation. Several protocols have been described for the isolation of the Golgi apparatus from liver tissue, but these are not suitable and not reproducible in harder tissues. Here, we describe a protocol to isolate Golgi vesicles from cardiac tissue using a discontinuous sucrose gradient.For complete details on the use and execution of this protocol, please refer to Tarazon et al. (2017).